Simplifying

x + -6= 9

Reorder the terms:

-6 + x = 9

Solving

-6 + x = 9

Solving for variable 'x'.

x + -6= 9

Reorder the terms:

-6 + x = 9

Solving

-6 + x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.

-6 + 6 + x = 9 + 6

Combine like terms: -6 + 6 = 0

0 + x = 9 + 6

x = 9 + 6

Combine like terms: 9 + 6 = 15

x = 15

Simplifying

x = 15

Add '6' to each side of the equation.

-6 + 6 + x = 9 + 6

Combine like terms: -6 + 6 = 0

0 + x = 9 + 6

x = 9 + 6

Combine like terms: 9 + 6 = 15

x = 15

Simplifying

x = 15

Answer would be: x - 6 = 9